A Re-Assessment of Security and Banditry in Kaduna State - Ekpo , Barnabas David; Izge, Na’ima Haruna (Kashere Journal of Politics and International Relations, 2023)
The security situation in Nigeria has been alarming since 1999, with violence pervading all geopolitical zones. Northwestern Nigeria has experienced significant violence, causing thousands of deaths. This paper will interrogate the factors driving banditry, its impact on national security, and government strategies to combat it; the paper adopted the pragmatic philosophy method and the Queer ladder theory to justify the subject of discourse. The primary focus of the paper is on two Local Government Areas; Birnin-Gwari and Kajuru, this is because of the rise and intensity of banditry and insecurity in the last six years (2016-2022) in the two local Government Areas of Kaduna state. The paper found that poverty, porous borders, unemployment, and lack of opportunities for youths to develop their talents, and the large expanse of forests that connects Niger and Katsina state which have international boundaries with Niger Republic and Chad are major drivers of banditry, and insecurity in Kaduna state. Bandits often recruit, indoctrinate and entice unemployed youths with money to join their groups. The paper also revealed that the security architecture in Birnin-Gwari and Kajuru LGAs is weak, with limited presence and capacity of security agencies to respond to threats. The area's difficult terrain is a challenge for security agencies to operate effectively. Therefore, this paper recommends, among others, that the government should equip the security agencies with appropriate modern equipment to improve their performance.